Using qualitative research methods to identify problems faced by adolescent girls in rural Andhra Pradesh - Koneru, Geethika; Rao, N. S. Sanjeeva; Swapna, B.; Sai, T. S. R. (International Journal Of Community Medicine And Public Health, 2020)
Background: Adolescence lays the foundation for physical wellbeing, emotional stability and mental ability. Quantitative methods often lack depth of understanding on crucial issues and leave many lacunae in the information available about the problems faced by adolescent girls in India. Using qualitative methods, a researcher can go beyond the surface and gather hidden information and associated feelings. Objective of the research was to qualitatively assess the knowledge, attitude and practices of health among adolescent girls (15-19 years) living in a rural area. Methods: This qualitative study to explore issues surrounding the health of adolescent girls in a rural area was conducted from August 2018 to November 2018 in the rural field practice area of the NRI Medical College. The qualitative methods used to gather information were focus group discussions (FGDs) and in-depth interviews (IDIs). Triangulation of information was done through key informant interviews (KIIs) with professionals working with adolescents. Results: The themes identified were causes of stress, education & marriage, safe pregnancy, prevalent diseases, exercise and leisure, health seeking behaviour and domestic violence. In-depth interviews with girls having significant social and psychological risk factors revealed a sense of loss of freedom, decision making power and resignation to their fate. Key informants revealed the neglect of adolescents in health programmes. Conclusions: Adolescent girls have poor knowledge about important health issues. Interventions that focus both on the continuation of the girls’ education and creating options for generating income are necessary along with non-judgmental counseling services and adolescent friendly health care facilities.